Surgical Decision-Making in Familial Adenomatous Polyposis - Steinberger, Allie E.; Westfal, Maggie L.; Wise, Paul E. (Clinics in Colon and Rectal Surgery, 2023)
Familial adenomatous polyposis (FAP) is an autosomal dominant disorder affecting patients with germline mutations of the adenomatous polyposis coli (APC) tumor suppressor gene. The surgical treatment of colorectal disease in FAP, which has the goal of colorectal cancer prevention, varies based on both patient and disease factors but can include the following: total colectomy with ileorectal anastomosis, proctocolectomy with stapled or hand-sewn ileal pouch-anal anastomosis, or total proctocolectomy with end ileostomy. The operative options and extent of resection, as well as the use of endoscopy and chemoprevention for the management of polyposis, will be discussed in detail in this article. In addition, commonly debated management decisions related to the treatment of patients with FAP, including the timing of prophylactic colorectal resections for patients with FAP and management of the polyp burden in the rectum, will be discussed. Finally, genotype considerations and the impact of desmoid disease on operative decisions in the setting of FAP will also be reviewed.
Keywords: familial adenomatous polyposis; proctocolectomy; adenomatous polyposis coli; desmoid